2013
DOI: 10.1002/ajmg.a.36052
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and young adults with down syndrome presenting to a medical clinic with depression: Co‐morbid obstructive sleep apnea

Abstract: Adolescents and young adults with Down syndrome (DS) sometimes experience new-onset mood disorder and decline in adaptive skills. The clinical phenomenon is poorly characterized and its pathogenesis is not understood. The possible contribution of obstructive sleep apnea syndrome (OSAS) to this phenomenon has not been studied. Subjects were ascertained as a convenience sample through our clinic for persons with DS and medical or mental health concerns between 2004 and 2009. When mood symptoms were present an ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 39 publications
2
37
0
1
Order By: Relevance
“…Many individuals with DS experience high rates of sleep problems, including obstructive sleep apnea, reduced REM sleep, and poor sleep initiation and maintenance [Stores et al, ; Harvey and Kennedy, ; Dykens, ; Capone et al, ]. These difficulties are associated with significantly poorer performance on tasks of attention and EF [Beebe and Gozal, ; Chen et al, ; Breslin et al, ], as well as memory storage/consolidation [Breslin et al, ], and may exist in the context of co‐morbid depression [Capone et al, ]. Proper sleep hygiene and interventions are an essential component to optimizing cognitive functioning.…”
Section: Unique Characteristics Of the Down Syndrome Populationmentioning
confidence: 99%
“…Many individuals with DS experience high rates of sleep problems, including obstructive sleep apnea, reduced REM sleep, and poor sleep initiation and maintenance [Stores et al, ; Harvey and Kennedy, ; Dykens, ; Capone et al, ]. These difficulties are associated with significantly poorer performance on tasks of attention and EF [Beebe and Gozal, ; Chen et al, ; Breslin et al, ], as well as memory storage/consolidation [Breslin et al, ], and may exist in the context of co‐morbid depression [Capone et al, ]. Proper sleep hygiene and interventions are an essential component to optimizing cognitive functioning.…”
Section: Unique Characteristics Of the Down Syndrome Populationmentioning
confidence: 99%
“…Furthermore, we did not include patients with non-treated sleep apnea. Capone et al [23] reported 25 patients with major depressive episodes with functional decline in 68% of them. Twenty-four (86%) of them had OSA compared to 44% of controls without depression.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 28 adolescents and young adults with Down syndrome, who were diagnosed with major depression by a mental health clinic for people with Down syndrome, found that 86% had OSAHS when tested by polysomnography, in comparison with 44% of nondepressed controls. Moderate to severe OSAHS was evident in 54% of cases and 11% of controls [37]. …”
Section: Comorbid Down Syndrome and Osahsmentioning
confidence: 99%